Rethinking security: the human side of risk management - Suslov, Tymur (Palgrave Pivot, 2025)
"This short Pivot argues for a paradigm shift towards a human-centric approach, emphasising the importance of understanding and managing human behaviour as a fundamental aspect of effective security strategies. It explores the intersection of psychology, criminology, and security, providing a comprehensive framework for integrating behavioural insights into security practices. The book questions the dependence on technology solutions and provides a new viewpoint, emphasising human behaviour as the core cause of security challenges. It explains complex psychological and criminological insights and provides straightforward explanations of psychological and criminological ideas that are critical to comprehending security issues. It advocates for paradigm shift in security practices and encourages a move from control-based to cooperative security paradigms." --